Success with inclusion : - Hannell, Glynis (Routledge, 2007)
Today's classroom welcomes diversity, where many levels, speeds and styles of learning coexist.nbsp; Success with Inclusion nbsp;provides over 1000 specific strategies to help identified areas of difficulty or advanced development. Using this book, teachers will be able to: quickly and easily identify and record their pupils? individual learning patterns using the observation charts provided structure a well planned inclusive environment implement creative and thoughtful learning interventions. create an atmosphere of flexibility and compassion. Author and experienced teacher Glynis Hannell gets down to the nitty gritty with chapters full of practical and creative ideas that will help accommodate not only pupils with difficulties but also those who are advanced. Learning strategies here will help you to: be an effective inclusive teacher address a variety of readingdifficulties support pupils' writing skills make maths comprehensible, fun and relevant enhance pupils' concentration encourage habits of organisation foster teamwork between yourself, colleagues, parents and pupils. The 42 photocopiable worksheets, checklists, charts, games and planners are provided in the appendix to give teachers a headstart. Also here are observation charts, literacy and maths resources, as well as support materials for teachers, pupils and parents.